Molybdenum, phosphorus, and pH do not constrain nitrogen fixation in a tropical forest in the southeastern Amazon. Issue 1 (15th December 2020) - Wong, Michelle Y.; Neill, Christopher; Marino, Roxanne; Silvério, Divino; Howarth, Robert W.
Abstract: High rates of biological nitrogen fixation (BNF) are commonly reported for tropical forests, but most studies have been conducted in regions that receive substantial inputs of molybdenum (Mo) from atmospheric dust and sea‐salt aerosols. Even in these regions, the low availability of Mo can constrain free‐living BNF catalyzed by heterotrophic bacteria and archaea. We hypothesized that in regions where atmospheric inputs of Mo are low and soils are highly weathered, such as the southeastern Amazon, Mo would constrain BNF. We also hypothesized that the high soil acidity, characteristic of the Amazon Basin, would further constrain Mo availability and therefore soil BNF. We conducted two field experiments across the wet and dry seasons, adding Mo, phosphorus (P), and lime alone and in combination to the forest floor in the southeastern Amazon. We sampled soils and litter immediately, and then weeks and months after the applications, and measured Mo and P availability through resin extractions and BNF with the acetylene reduction assay. The experimental additions of Mo and P increased their availability and the lime increased soil pH. While the combination of Mo and P increased BNF at some time points, BNF rates did not increase strongly or consistently across the study as a whole, suggesting that Mo, P, and soil pH are not the dominant controls over BNF. In a separate short‐term laboratory experiment, BNF did not respond strongly to Mo and P even when labile carbon was added. We postulate that high nitrogen (N) availability in this area of the Amazon, as indicated by the stoichiometry of soils and vegetation and the high nitrate soil stocks, likely suppresses BNF at this site. These patterns may also extend across highly weathered soils with high N availability in other topographically stable regions of the tropics.